6-7x=61-42x

Simple and best practice solution for 6-7x=61-42x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-7x=61-42x equation:


Simplifying
6 + -7x = 61 + -42x

Solving
6 + -7x = 61 + -42x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '42x' to each side of the equation.
6 + -7x + 42x = 61 + -42x + 42x

Combine like terms: -7x + 42x = 35x
6 + 35x = 61 + -42x + 42x

Combine like terms: -42x + 42x = 0
6 + 35x = 61 + 0
6 + 35x = 61

Add '-6' to each side of the equation.
6 + -6 + 35x = 61 + -6

Combine like terms: 6 + -6 = 0
0 + 35x = 61 + -6
35x = 61 + -6

Combine like terms: 61 + -6 = 55
35x = 55

Divide each side by '35'.
x = 1.571428571

Simplifying
x = 1.571428571

See similar equations:

| (x+4)(x-12)=x(x-9) | | 3(x-7)-4=-19 | | 10x+15-20x=5 | | -68-6x=9x+17 | | w+(w+10)+50=180 | | 44-5x=4x+21 | | 10a-14+6=-12 | | x^2-9x+18/2x^2-9x+9 | | 20-x=5 | | -8x+4=26x-1 | | 7x-14=5x+42 | | ln(x-4)=2 | | 118-2x=43x+18 | | 1/2ln(5x)=4 | | 14k-6-10k=6 | | 2x+9=-27+7 | | 2a^2+24=0 | | 40m-48+24m=16 | | 9x-5=7-4x | | x^2-3+7=0 | | x-3=7x+1 | | 4+a=b | | 6-10x=87-31x | | 5q^2-4q=4q^2-4q+21 | | x-6=3x+24 | | 4x-21=6x-3 | | 2x-4-5x=-x+5+7x-3 | | 2m^2-3m-35=0 | | 3(4x+2)=x-28 | | -x^2-x+2=2 | | 3x^2+10x+8=2 | | 4(4x+5)=21x+19-5x+1 |

Equations solver categories